Bovine Mastitis Caused by Multidrug-Resistant Nocardia farcinica - Pereira de Oliveira, Raylson; Francelino Dias, Rômulo Freitas; da Silva, Renato Amorim; Bandeira de Melo, Renata Pimentel; Cabral de Araujo, Carolina Akiko Sato; Nogueira, Joel Fonseca; da Costa, Mateus Matiuzzi; Pinheiro Junior, José Wilton; Mota, Rinaldo Aparecido (Acta Scientiae Veterinariae, 2020)
Background: Mastitis caused by Nocardia is characterized by pyogranulomatous inflammation related to inadequate hygiene conditions and is difficult to treat. Prompted by the absence of documentation of Nocardia farcinica associated to bovine mastitis in the Northeast region of Brazil, this is the first report to describe bovine mastitis caused by multidrug-resistant N. farcinica. Case: Four milk samples (one from each teat) obtained from a 3-year-old Jersey cow raised on a property located in the metropolitan region of Recife, Pernambuco state, Brazil, were submitted to the Laboratory of Infectious-Contagious Diseases of the Veterinary Hospital at Universidade Federal Rural de Pernambuco. At the laboratory, samples were cultured in base agar enriched with 7% sheep blood (blood agar) in a microbiological incubator at 37°C under aerobic conditions for 72 h. After only 48 h, however, pure bacterial colony growth was observed in all samples. Macroscopic analysis revealed small colonies, with an irregular shape, dry aspect, and greyish in color. Gram-positive rods forming filaments and/or ramifications were observed using a Gram staining method. Nocardia spp. were identified according to morphotinctorial characteristics. Susceptibility testing using the disc-diffusion method in agar (antibiogram) was performed using the following antibiotics: penicillin (10 IU), tetracycline (30 µg), amoxicillin (10 µg), gentamicin (10 µg), cephalexin (30 µg), erythromycin (15 µg), cephalothin (30 µg) and ampicillin (30 µg). However, the organism exhibited resistance to all drugs; as such, a new milk sample was obtained at the same location the initial samples were collected. Samples (approximately 5 mL) were collected aseptically and separately from all four teats in sterile bottles, during which the presence of granular material was noted. Bacterial culture was performed as previously described and, after 48 h, colony growth with the same characteristics as the first isolation were observed, and with same morphotinctorial characteristics in the Gram stain. A resistance profile was observed for 14 of the antimicrobial drugs tested; sensitivity was verified only for ciprofloxacin and amoxicillin with clavulanic acid. One bacterial colony was selected and sent to the Center of Strategic Technology of Northeast (CETENE-PE) for species identification using a matrix-associated laser desorption ionization-time of flight (MALDI-TOF/MS) technique, which confirmed the species to be N. farcinica. Molecular characterization of 16s ribosomal DNA was performed using polymerase chain reaction with universal prokaryotic primers 516F-13R. Subsequently, the amplified product was subjected to sequencing, and the result was analyzed for quality using Phred base calling software; bases with a Phred value > 20 were kept. The sequence was evaluated using GenBank, in which the isolate exhibited 99% similarity to N. farcinica. Discussion: Clinical findings and animal history associated with microbiological culture and bacterial identification using the MALDI-TOF technique, as well as DNA sequencing, confirmed the case of clinical mastitis to be caused by N. farcinica. These bacteria are considered saprophytes, and their occurrence is associated with deficiencies in hygienic-sanitary management, such as not using pre- and post-dipping, which may favor mammary gland infection. Treatment of N. farcinica mastitis is effective only when properly performed, with agent identification and antibiotic sensitivity tests in vitro associated with the adoption of hygienic-sanitary measures. This is the first description of bovine mastitis caused by N. farcinica in the northeast of Brazil. Multidrug resistance should raise awareness of producers searching for laboratory aids in agent identification as well as antibiotic sensitivity tests, and to develop a proper therapeutic protocol based on results obtained in laboratory examinations.